Penguatan Moderasi Beragama dalam Kurikulum PAI : Studi Literatur terhadap Tantangan dan Peluang di Era Digital - Ifa Afida; Nur Wahidah; Yovita Dyah Permatasari (STIKes Ibnu Sina Ajibarang, 2025)
Religious moderation is an important concept in Islamic Religious Education (PAI), especially in the digital era that brings challenges such as the spread of extreme ideologies through the internet and the low digital literacy of students. This study aims to analyze the challenges and opportunities of strengthening religious moderation through the PAI curriculum and offer technology-based strategies. The research method uses a qualitative approach with a literature review. Data were obtained from various literatures, such as scientific journals, books, and policy documents, which were analyzed using the content analysis method. The results showed that the main challenges include lack of digital literacy, resistance to change, and limited supporting resources. On the other hand, opportunities include the utilization of digital technologies such as online learning platforms, social media, and technology-based educational content to convey moderation values in an attractive manner. Recommended strategies include the integration of moderation values in the curriculum, strengthening teacher competencies through digital training, and collaboration with various stakeholders. This research makes a novel contribution by integrating the challenges and opportunities of the digital era into the approach of strengthening religious moderation. The findings are expected to serve as a foundation for policymakers in creating a more adaptive and relevant PAI curriculum in the digital era.